The Effect of Using Picture Series in Teaching Narrative Text - Mardiana, Mardiana; Nurpahmi, Sitti; Satriani, Wiwi (English Language Teaching for EFL Learners Journal, 2023)
The aim of this research is to find out the effectiveness of using picture series in teaching writing narrative text. The research problem is “To what extent is the use of picture series effective in teaching writing narrative text to the first year students at MAN 1 Makassar”. It is quasi-experimental research. The population is 439 students.The researcher uses purposive sampling technique in selecting the sample. The sample of this research is consisted of 79 students which divide into X MIA 1 as the experimental class and X MIA 2 as the controlled class. The data collection procedures is conducted by giving pre-test, treatment and post-test. In the first meeting, the researcher gives pre-test. Treatment is conducted by teaching narrative text using picture series in the experimental class which took six times meeting. The controlled class and experimental class are taught the same topic of narrative text. In the last meeting, the researcher gives post-test. The data is analyzed by using SPSS. The research findings shows that students obtain score on pre-test with the mean score 58.60 an d on the post-test with the mean score 78.67 as good classification. It is proved by the result of the statistical analysis of the level significance 0.05 with degree of freedom (df) 38 indicated t-test values of the students’ writing narrative text (3.293) is higher than t-table value (2.024). The effectiveness of picture series also can be seen from the effectiveness test. Afterwards, the results of the test is 0.47 (R<1). Based on the result of analysis, the researcher concludes that the use of picture series is effective in writing narrative text. The researcher finds that picture series helped the students in generating ideas. It shows that picture series can be an effective media in writing narrative text.